(untitled) (Tạp chí Y học Cộng đồng, 2024)
Aim: To assess the effectiveness of targeted interventions to improve health care workers (HCWs)’ knowledge of COVID-19 patient safety at Dien Bien Provincial General Hospital. Methods: A pre- and post-intervention study was conducted among 275 full-time HCWs at Dien Bien Provincial General Hospital from July 2021 to July 2022. Participants attended five structured training sessions focused on patient safety and COVID-19 prevention, including personal protective equipment (PPE) use and hand hygiene. Knowledge was measured using a questionnaire based on Vietnam’s Ministry of Health patient safety guidelines. Data were analyzed using SPSS 22.0, with statistical significance set at p < 0.05. Results: The intervention led to significant improvements in HCWs’ knowledge of COVID-19 prevention measures. Compliance with mask-wearing increased from 86.9% to 92.7%, and knowledge scores for infection control measures rose substantially. Standard precautions improved from 72.0% to 85.1%, and transmission-based precautions from 47.6% to 76.4%. Mean knowledge scores increased across general prevention (1.71 to 1.81), infection control (2.87 to 3.90), and laundry handling (5.32 to 6.29) domains. Conclusion: The targeted training interventions successfully increased HCWs’ adherence to essential COVID-19 prevention protocols, demonstrating the potential of similar programs to improve healthcare safety in Vietnam. Continuous education is recommended to sustain high compliance and address logistical barriers in infection control practices.